PENGGUNAAN METODE PERMAINAN KARTU KATA BERGAMBAR DALAM PENINGKATAN MINAT BELAJAR SISWA - Sabri Sabri; Mandasari Dalimunthe (DIRASATUL IBTIDAIYAH, 2021)
AbstractThis study aims to determine whether the use of the picture word card game method can increase the interest in learning Citizenship Education in class IV MIN 2 Padangsidimpuan students. This research is a classroom action research. This study uses a qualitative method. The subjects in this study were class IV A with 38 students. The data collection instruments used were questionnaires and observations. Data analysis used a quantitative approach with statistical methods. Based on the research carried out, it was concluded that the interest in learning Citizenship Education in class IV A students could be increased by using the picture word card game method. This increase can be seen from the results of questionnaires and observations. The results of the action using a questionnaire in cycle I with an average value of 97.31, cycle II 104.86, and cycle III 113.65. While the results of the action using observations in the first cycle was 86.83%, the second cycle was 91.44%, and the third cycle was 95.39%. Judging from the results of the action cycle I to cycle III there is an increase in the number of values which indicates an increase in interest in learning Citizenship Education. Keywords: Picture Word Card Game Method; Interest to learn; Citizenship Education